Pelatihan Pengolahan Sirup dan Selai Jambu Biji Merah di Desa Ciasihan, Bogor, Jawa Barat - Dari, Dini Wulan; Monasdir, Monasdir; Shalita, Assya; Elviandri, Yoni; Ramlan, Ramlan; Fauziah, Syarah Asma; Pandayu, Harits Yowansyah; Reza, Muhammad Aulia; Habibullah, Alfata Ma’ruf; Susilawati, Etic; Putra, Gilang Tresna; Himmah, Maihardiyanti Faiqotul; Fajriyah, Afifathu Rahmah (Universitas Baiturrahim, 2024)
Red guava is a highly perishable fruit that poses significant risks of loss for farmers, necessitating further processing to extend its shelf life. One effective method of processing is the production of guava jam and syrup. A training program was conducted to educate participants, specifically Family Welfare Empowerment (PKK) mothers and the MSME group in Ciasihan Village, Bogor Regency, on producing these products using guava, sugar, water, citric acid, and agar. Granulated sugar serves both as a sweetener and a natural preservative in the syrup. The training aimed to empower participants to utilize their free time productively and transform lower-grade guava into marketable products, thereby reducing agricultural waste. Methods included demonstrations and consultations on syrup and jam-making processes. The training resulted in a significant increase in knowledge among PKK and MSME members regarding guava processing techniques. This initiative has the potential to enhance local economic development by converting neglected fruit into valuable products. However, ongoing support is necessary for further development. Additionally, this training may facilitate the establishment of distinctive local businesses and products specific to Ciasihan Village. By harnessing local resources and knowledge, this program not only addresses food waste but also promotes sustainable entrepreneurship within the community.